Examining the Impact of Transformational Leadership and Work Environment on Employee Performance through Work Motivation - Candra, Viky Adi; Soni, Soni; Emma, Emma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the impact of transformational leadership style and work environment on employee performance, with work motivation serving as an intervening variable, at PT BPR Bank Jombang (Perseroda). The research adopts a quantitative approach using a survey method. The population comprises all employees of PT BPR Bank Jombang (Perseroda), while the sample was selected through purposive sampling. A total of 120 employees with a minimum of one year of work experience participated as respondents. Data were collected using structured questionnaires and analyzed through path analysis to assess both direct and indirect relationships among the variables. The findings reveal that transformational leadership has a positive and significant effect on both work motivation and employee performance. Similarly, the work environment exerts a positive and significant influence on work motivation and employee performance. In addition, work motivation is found to have a positive and significant effect on employee performance. However, the mediation analysis indicates that work motivation does not significantly mediate the relationship between transformational leadership and employee performance, nor between the work environment and employee performance. These results suggest that employee performance is more strongly influenced by the direct effects of transformational leadership and work environment than by indirect effects through work motivation. This study provides practical insights for regional banking management in formulating leadership strategies and creating a conducive work environment to enhance employee performance in a sustainable manner.